Distinct neuronal processes in the ventromedial prefrontal cortex mediate changes in attention load and nicotine pro-cognitive effects in male rats - Vouillac-Mendoza, Caroline; Biendon, Nathalie; Dovero, Sandra; Guillem, Karine (Frontiers in Neural Circuits, 2025)
The prefrontal cortex (PFC) plays a key role in attention. In particular, neuronal activity in the ventromedial PFC (vmPFC) has been implicated in the preparatory attentional period that immediately precedes cue presentation. However, whether vmPFC neuronal activity during this preparatory period is also sensitive to changes in task demand and to the pro-cognitive effects of nicotine remained to be investigated. Here, we used in vivo electrophysiology to record vmPFC neuronal activity in rats during two distinct manipulations: a task manipulation that increased task demand by reducing the cue stimulus duration (from 1 to 0.5 s), and a pharmacological manipulation by administrating an acute nicotine injection (10 μg/inj, i.v.) before the session. We found that increasing task demand decreased attentional performances and vmPFC precue neuronal activity, but had no effect on gamma oscillations. In contrast, nicotine injection increased attention and gamma oscillations, but almost abolished vmPFC phasic precue responses. Together, these findings indicate the existence of two distinct neuronal processes operating at different timescales and suggests that allocation of attention could be achieved through multiple neuronal mechanisms within the vmPFC.